Comparative studies on metabolic profile of anestrus and normal cyclic Haryana cows - SINGH, C P; SAXENA, ATUL; PRASAD, SHIV; PRASAD, J K (The Indian Journal of Animal Reproduction, 2023)
Twenty seven Haryana cows were selected (17- anestrus & 10- nonnal cyclic) from the university farm for the study of metabolic profile in relation to anestrus. Parameter studied were haemoglobin (Hb ), serum glucose, total protein, calcium (Ca), inorganic phosphorus (Pi) and calcium to phosphorus ratio (Ca: P). It was found that levels ofHb were significantly higher (P<0.01) in nonnal cyclic cows C()mpared to anestrus. An overall (day 0 to day 20) increase of Hb concentration and serum glucose were non-significantly higher in respective groups. Contrary to these increased values ofHb and glucose in normal cyclic cows, significantly higher levels of Pi (P<0.01) and total protein (P<0.05) were recorded in anestrus cows compared to normal cyclic cows. Calcium was also non-significantly higher in anestrus cows compared to nonnal cyclic cows. Calcium to phosphorus ratio was better in nonnal cyclic cows than anestrus cows which were 2.04:1 and 1.52:1, respectively. Such metabolic profile would be helpful in assessing the status of nutrition and its impact on infertility.